Causal relationship of liposomes and circulating metabolomes to schizophrenia： a two-step， two-sample Mendelian randomization study - Lei Mengyun; Du Yanhong; Gao Yao; Deng Huaili; Wang Binhong; Ren Zhiyong; Liu Sha (Sichuan jingshen weisheng, 2025)
BackgroundSchizophrenia is a complex， chronic and severe mental disorder， and the pathogenesis of which has not been fully elucidated. The abnormalities in lipid metabolism and circulating metabolomes have already been implicated in the pathophysiology of schizophrenia. However， available studies have mainly focused on a few liposomes and circulating metabolites， failing to systematically reveal the mediating role of circulating metabolomes in the causal relationship between liposomes and schizophrenia.ObjectiveTo uncover mediating role of circulating metabolomes in the causal relationship between liposomes and schizophrenia， thereby providing biomarkers and potential therapeutic targets for the prevention and treatment of schizophrenia.MethodsData from Genome-Wide Association Studies （GWAS） were analyzed， taking data on 179 liposomes as exposure variables， data on 123 circulating metabolites as intermediate variables， and data on schizophrenia as outcome variable. A two-step， two-sample Mendelian randomization analysis was conducted using the inverse-variance weighted （IVW）， MR- Egger， Weighted median， and Weighted mode methods to study the causal relationship of liposomes with schizophrenia and the mediating role of circulating metabolomes in the relationship.ResultsIVW model identified 8 lipids associated with schizophrenia without reverse causality. There were 5 circulating metabolomes strongly associated with schizophrenia. Acetate played a significant mediating role in the causal relationship between phosphatidylinositol （18：0_18：2） and schizophrenia （P=0.023， 95% CI： 0.036~0.532）， accounting for 28.4% of the causal relationship.ConclusionThis study demonstrates a causal relationship between liposomes and schizophrenia， with phosphatidylinositol being a risk factor in the progression of schizophrenia， and acetate playing a mediating role in this process. ［Fund by National Natural Science Foundation of China General Program （number， 82271546）； Shanxi Merit Funding for Overseas Students Sci-Tech Activities Project （number， 20240041）； Shanxi Province Science and Technology Innovation Leading Talent Team Project （number， 202304051001049）； Shanxi Scientific Research Foundation for the Returned Overseas Chinese Scholars （number， 2022-190）； "Six Measures for Health Care Prosperity" Specialized Research Program （number， Y2024008）］